{4,4′-Dimethoxy-2,2′-[1,1′-(ethane-1,2-diyldinitrilo)diethylidyne]diphenolato}nickel(II) hemihydrate - Fun, Hoong-Kun (International Union of Crystallography, 2008)
In the title complex, [Ni(C(20)H(22)N(2)O(4))]·0.5H(2)O, the Ni(II) ion is in a slightly distorted square-planar geometry involving an N(2)O(2) atom set of the tetradentate Schiff base ligand. The asymmetric unit contains one molecule of the complex and half a water solvent molecule. The solvent water molecule lies on a crystallographic twofold rotation axis. An intermolecular O—H⋯O hydrogen bond forms an R (2) (1)(4) ring motif involving a bifurcated hydrogen bond to the phenolate O atoms of the complex. In the crystal structure, molecules are linked by π–π stacking interactions, with centroid–centroid distances in the range 3.5310 (11)–3.7905 (12) Å, forming extended chains along the b axis. In addition, there are Ni⋯Ni and Ni⋯N interactions [3.4404 (4)–4.1588 (4) and 3.383 (2)–3.756 (2) Å, respectively] which are shorter than the sum of the van der Waals radii of the relevant atoms. Further stabilization of the crystal structure is attained by weak intermolecular C—H⋯O and C—H⋯π interactions.